Shed writing at Sheila Ryan’s. - McGuire, Andrea (2014)
A message written on Sheila Ryan’s shed. “May 20/13. Almost arrived. Having a time of my life. Be back July 15/13. Good ridden’s NS. God is Good. Loving my moment with brother Mike and sister in law Sheila.”